Crystal Structures of D-N-(2-Adamantyl)phenylglycinol and L-N-(2-Adamantyl)diphenylphenylalinol: Chiral Amino Alcohols Utilized as Ligands for Catalytic Asymmetric Hydroamination - Reinheimer, E. W.; Kohn, A. W.; Groeneman, R. H.; Krueger, H. R.; Kantardjieff, K.; Johnson, A. R. (Molecular Crystals and Liquid Crystals, 2016)
Amino alcohols are important ligands for the asymmetric catalytic hydroamination of aminoallenes to form chiral pyrrolidines. Herein, we report the crystal structures of two chiral amino alcohols, D-N-(2-Adamantyl)phenylglycinol and L-N-(2-Adamantyl)diphenylphenylalinol, that function as ligands within transition metal complexes that catalyze the hydroamination of aminoallenes. Both molecules crystallize in the noncentrosymmetric orthorhombic space group P2 1 2 1 2 1 . Inter- and intramolecular hydrogen bonding plays an important role in stabilizing each alcohol in the solid state in the absence of a transition metal. The presence of these hydrogen bonds has been verified by single crystal X-ray diffraction and their overall strength determined by computational methods.